Who is an African? race, identity, and destiny in post-apartheid South Africa - Kaunda, Chammah (Chammah J.); Hewitt, Roderick R.; Murphree, Marshall W.; Hlongwa, Nobuhle (Lexington Books/Fortress Academic, 2018)
This book is an in-depth conversation and study about issues of African identity in South Africa. It aims to inform policy development and change in the role of race and ethnic identity within the ""rainbow"" configuration of nation building.